Mutans Streptococci and Removable Orthodontics - Kasem Ahmed Abeas1, Zainab Al-Mahdi2, Issam Merza3, Lamis Khudir4 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Numerous studies have investigated the influence of orthodontic therapy and appliances on the oral microbial flora. Little is known about the effect of removable orthodontic appliances on oral colonisation by mutans streptococci. The original aim of the present investigation was to assess the mean and the statistical mean difference of colony values of S. Mutans in a removable orthodontic appliance fabricated from two types of acrylic resin for an Iraqi sample. According to certain predetermined sample criteria; the present study consist of eleven consecutive young patients scheduled for orthodontic treatment with removable orthodontic appliances at the department of orthodontics at the college of dentistry/ University of babylon as well as dental student seeking orthodontic treatment. Each subject included in the present study had to wear an upper (hot cured) and lower (cold cured) well adaptive removable orthodontic appliance. A swab was taken from the lingual/palatal gingival and inoculated within the brain heart agar then cultured within Mitis- Salivarius Bacitracin (MSB) agar. The colonies were calculated for each plate, afterwards the colony forming unit (CFU) will be calculated. of the present study showing that all bacterial colony values were higher in the lower than upper arch. However, a statistical non significant difference was registered between the colony mean values of both arches. The present study signify both types of acrylic resins (heat/ cold) can be used as an orthodontic acrylic base in removable appliances within the orthodontic practice with a careful monitoring of patients treated orthodontically for risk of caries development.